Competition law and policy in the European Union some lessons from Southeast Asia - Briguglio, Lino (The Philippine Review of Economics, 2013)
This paper describes the main thrust of competition law and policy in the European Union (EU) from which it draws some lessons for the Association of Southeast Asian Nations (Asean), mainly with regard to the development of a single market in the region. The paper argues that the success of competition law and policy in the EU to further strengthen the single market can be attributed mainly to the fact that member countries accepted to forgo part of their sovereignty to the union, and to allow a central entity (the European Commission) to enforce competition law, with investigative powers, backed by an EU-wide legislative framework transposed into national laws. The paper contends that the creation of an ASEAN single market by 2015 is not likely to be attained due to weaknesses in the institutional framework relating to competition law and policy within the region, particularly because of weak enforcement across the region.